Preparation method of spherical catalyst and application of spherical catalyst in tubular reactor

By mixing the molecular sieve catalyst with the binder and extruder, and after extrusion, crushing and granulation and spherical mold forming, the problem of uneven shape in the preparation of molecular sieve catalyst is solved, the preparation of spherical catalyst is realized, and the strength and reaction efficiency of the catalyst are improved.

CN119819381APending Publication Date: 2025-04-15YANCHANG ZHONGKE (DALIAN) ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722237.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In traditional preparation methods, molecular sieve catalysts have problems of uneven length and diameter, resulting in uneven stacking, inconsistent distribution in reactor tubes, and inability to meet the requirements.

Method used

The catalyst is mixed with a binder and an extruder, added inorganic acid, and then extruded into a thick strip through the orifice plate, crushed and granulated, and then sieved, and then placed in a spherical mold for pressing and forming. Finally, the spherical catalyst is obtained by drying and baking.

Benefits of technology

The obtained spherical catalyst has a unified shape and size, which improves the strength and uniformity of the catalyst, enhances the flowability and reaction efficiency in the reactor tube, ensures the consistency of reaction conditions, and effectively improves the reaction activity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158527110000061
    Figure BDA0005158527110000061
  • Figure BDA0005158527110000071
    Figure BDA0005158527110000071
  • Figure BDA0005158527110000091
    Figure BDA0005158527110000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a spherical catalyst and application of the spherical catalyst in a tubular reactor, and the preparation method at least comprises the following steps: I, uniformly mixing the catalyst with a binder and an extrusion aid, and adding inorganic acid to obtain a mixed material; iI, extruding the mixed material obtained in the step I into thick strips through a pore plate, crushing in a crusher, granulating, and screening to obtain a small-particle sample; step III, putting the small-particle sample obtained in the step II into a spherical mold, and pressurizing to obtain a spherical sample; and IV, drying and roasting the spherical sample obtained in the step III to obtain the spherical catalyst. According to the preparation method provided by the invention, through simple and effective process steps, the problems existing in traditional catalyst preparation are remarkably improved, and the preparation method has wide application prospects and market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a spherical catalyst and application thereof in a tubular reactor, belonging to the field of catalyst preparation. Background Art

[0002] Spherical catalysts are widely used in the chemical industry due to their uniform stacking, good fluidity in the reactor tube, and high reaction activity. Spherical catalysts have a higher stacking density than general irregular catalysts. Spherical catalysts can roll and are easy to load. Generally, they do not produce "bridging" phenomena, which avoids side reactions caused by local hot spots caused by uneven loading. The gaps between spherical catalyst particles are evenly distributed, which can effectively reduce the pressure drop in the reactor. The surface of spherical catalysts is smooth, without edges and corners, and has good wear resistance. There is less dust generated during loading or use, and the loss is small. Spherical catalysts have less resistance to airflow, and the airflow is evenly distributed during use, and the temperature difference between the planes is small, which is conducive to improving production capacity.

[0003] Molecular sieves are inorganic crystalline materials with regular pores. The secondary structural units are composed of skeleton T atoms and oxygen atoms, which then construct the pores and cages of the molecular sieve to form a specific skeleton structure. Molecular sieves have become widely used catalytic materials because of their regular pores, adjustable acidity and extremely high stability.

[0004] Used as a catalytic material, molecular sieves need to be formed into a specific shape so that they can be loaded into industrial reactors. The reactor types are different, and the required particle shapes and sizes are also different. However, because molecular sieves do not have cohesiveness, it is generally necessary to add a binder to form a cylindrical shape by extrusion molding, but there are serious problems of uneven length and diameter. In traditional preparation methods, common problems include uneven stacking, inconsistent distribution in the reactor tube, and the inability of the reaction activity to meet the requirements. In this regard, the present application provides a method for preparing a spherical catalyst, and the spherical catalyst obtained by the preparation method has a uniform shape and size, which ensures the consistency of the reaction conditions in the reactor tube. Summary of the invention

[0005] According to one aspect of the present application, a method for preparing a spherical catalyst is provided, comprising at least the following steps:

[0006] Step I: mixing the catalyst, the binder and the extrusion aid, adding an inorganic acid to obtain a mixed material;

[0007] Step II: The mixed material obtained in step I is squeezed into thick strips through a perforated plate, crushed in a pulverizer, granulated and sieved to obtain a small particle sample;

[0008] Step III: placing the small particle sample obtained in step II into a spherical mold and applying pressure to obtain a spherical sample;

[0009] Step IV: drying and calcining the spherical sample obtained in step III to obtain a spherical catalyst.

[0010] Optionally, the catalyst is selected from at least one of hydrogen-type zeolite, heteroatom-containing SUZ-4 zeolite, molecular sieve catalyst, non-metal modified molecular sieve catalyst, and metal modified molecular sieve catalyst;

[0011] Optionally, the molecular sieve catalyst is selected from at least one of ZSM-5 molecular sieve, HY molecular sieve, H-MOR molecular sieve, 13X molecular sieve and NaY molecular sieve.

[0012] Optionally, the metal in the metal-modified molecular sieve catalyst is selected from at least one of iron, cobalt, nickel, copper, silver and zinc.

[0013] Optionally, the inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.

[0014] Optionally, the binder is selected from at least one of pseudo-boehmite, silica sol, aluminum sol, γ-alumina, and kaolin.

[0015] Optionally, the extrusion aid is selected from at least one of solid paraffin, paraffin powder, magnesium stearate, calcium stearate, sodium stearate, sesbania powder, starch, glucose, cellulose, methyl cellulose, alkyl benzene sulfonate, liquid paraffin, and fatty alcohol polyoxyethylene ether.

[0016] Optionally, the pressurizing pressure is 0.1-300 kN.

[0017] Optionally, the pressurizing pressure is independently selected from any value among 0.1 kN, 10 kN, 20 kN, 30 kN, 40 kN, 50 kN, 60 kN, 70 kN, 80 kN, 90 kN, 100 kN, 200 kN, 300 kN or a range between any two of the above points.

[0018] Optionally, the pressurization time is 0.01 to 60 seconds.

[0019] Optionally, the pressurization time is independently selected from any value among 0.01s, 0.05s, 0.1s, 0.5s, 10s, 20s, 30s, 40s, 50s, 60s or a range value between any two of the above points.

[0020] Optionally, the drying conditions are as follows:

[0021] The drying temperature is 80-160°C;

[0022] The drying time is 3 to 6 hours.

[0023] Optionally, the calcination conditions are as follows:

[0024] The calcination temperature is 500-750°C;

[0025] The calcination time is 4 to 8 hours.

[0026] Optionally, the porosity of the spherical catalyst is 40-50%.

[0027] Optionally, the porosity of the spherical catalyst is independently selected from any value of 40.0%, 40.1%, 40.2%, 40.3%, 40.4%, 40.5%, 40.6%, 40.7%, 40.8%, 40.9%, 50.0% or a range between any two of the above points.

[0028] Optionally, the strength of the spherical catalyst is 100-250N / particle.

[0029] Optionally, the strength of the spherical catalyst is independently selected from any value of 100N / particle, 110N / particle, 120N / particle, 130N / particle, 140N / particle, 150N / particle, 160N / particle, 170N / particle, 190N / particle, 200N / particle, 210N / particle, 220N / particle, 230N / particle, 240N / particle, 250N / particle, or a range value between any two of the above points.

[0030] According to a second aspect of the present application, there is provided a use of a spherical catalyst in a shell-and-tube reactor.

[0031] The beneficial effects of this application include:

[0032] 1) The preparation method provided in the present application can obtain a catalyst with uniform spherical shape, enhance the strength and uniformity of the catalyst, increase the porosity of the catalyst particles, and promote the improvement of the fluidity and reaction efficiency in the reactor tube.

[0033] 2) The preparation method provided in the present application provides spherical catalysts with uniform shape and size, thus ensuring the consistency of reaction conditions in the reactor tube.

[0034] 3) The preparation method provided in the present application effectively improves the reaction activity of the catalyst, significantly enhances the reaction efficiency, effectively controls the by-products, and improves the selectivity. DETAILED DESCRIPTION

[0035] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0036] Unless otherwise specified, the raw materials and reagents in the examples of this application were purchased through commercial channels.

[0037] In the following Examples 1 to 10 and Comparative Examples 1 to 2, the catalysts prepared in each case were loaded into a tubular reactor to carry out the carbonylation of dimethyl ether to produce methyl acetate. The initial activity of the catalyst was investigated under standard evaluation conditions, with a reaction temperature of 188°C, a pressure of 2.0 MPa, a raw gas composition of DME:CO:H2=1:10:9, and a feed space velocity of GHSV=1800 h -1 , the test results are shown in Table 1.

[0038] Example 1

[0039] Weigh 60g of copper-containing mordenite catalyst, add 60g of aluminum sol, 1.5g of sesbania powder and mix well, add 1g of solid paraffin and 35g of dilute phosphoric acid, extrude into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 50kN, and maintained for 0.05 seconds to obtain a spherical catalyst precursor. Then it is dried at 120℃ for 6h, and calcined at 550℃ in 20ml / min air for 5 hours to obtain a spherical catalyst, recorded as catalyst 1#, and its catalytic performance is shown in Table 1.

[0040] Example 2

[0041] The catalyst was prepared according to the method described in Example 1, except that the 60 g catalyst weighed was a copper-cerium modified molecular sieve catalyst, denoted as catalyst 2#, and its catalytic performance is shown in Table 1.

[0042] Example 3

[0043] The catalyst was prepared according to the method described in Example 1, except that 0.5 g of liquid paraffin and 50 g of dilute phosphoric acid were used, and was recorded as catalyst 3#. Its catalytic performance is shown in Table 1.

[0044] Example 4

[0045] Weigh 60g of copper-containing mordenite catalyst, add 15g of kaolin, 1g of sesbania powder and mix well, add 1g of solid paraffin and 35g of dilute phosphoric acid, squeeze into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 100kN, and maintained for 0.2 seconds to obtain a spherical catalyst precursor. Then it is dried at 120℃ for 6h, and calcined at 550℃ in 20ml / min of air for 5 hours to obtain a spherical catalyst, recorded as catalyst 4#, and its catalytic performance is shown in Table 1.

[0046] Example 5

[0047] The catalyst was prepared according to the method described in Example 1, except that the inorganic acid was 50 g of dilute nitric acid, denoted as catalyst 5#, and its catalytic performance is shown in Table 1.

[0048] Example 6

[0049] The catalyst was prepared according to the method described in Example 1, except that the molding pressure was 50 MPa and the pressure was maintained for 1 second. It was denoted as catalyst 6#, and its catalytic performance is shown in Table 1.

[0050] Example 7

[0051] Weigh 60g of copper-cerium modified molecular sieve catalyst, add 60g of aluminum sol, 1.5g of sesbania powder and mix well, add 0.5g of calcium stearate and 35g of dilute phosphoric acid, squeeze into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 50kN, and maintained for 2 seconds to obtain a spherical catalyst precursor. Then it is dried at 120°C for 6 hours, and roasted at 550°C in 20ml / min of air for 5 hours to obtain a spherical catalyst, recorded as catalyst 7#, and its catalytic performance is shown in Table 1.

[0052] Example 8

[0053] A catalyst was prepared according to the method described in Example 7, except that 1 g of magnesium stearate and 50 g of dilute nitric acid were used, and was recorded as catalyst 8#. Its catalytic performance is shown in Table 1.

[0054] Example 9

[0055] Weigh 60g of copper-cerium modified molecular sieve catalyst, add 15g of silica sol, 1g of methyl cellulose and mix well, add 0.5g of fatty alcohol polyoxyethylene ether and 35g of dilute phosphoric acid, extrude into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 80kN, and maintained for 0.2 seconds to obtain a spherical catalyst precursor. Then it is dried at 120°C for 6h, and roasted at 550°C in 20ml / min air for 5 hours to obtain a spherical catalyst, recorded as catalyst 9#, and its catalytic performance is shown in Table 1.

[0056] Example 10

[0057] The catalyst was prepared according to the method described in Example 1, except that the molding pressure was 60 kN and the pressure was maintained for 1 s. It was denoted as catalyst 10#, and its catalytic performance is shown in Table 1.

[0058] Comparative Example 1:

[0059] 60g of copper-containing mordenite catalyst was weighed, 60g of aluminum sol and 1.5g of sesbania powder were added and mixed, 1g of solid paraffin and 35g of dilute phosphoric acid were added, and the mixture was extruded into strips through a strip plate at a pressure of 7MPa to obtain a spherical catalyst precursor. The mixture was then dried at 120°C for 6h and calcined at 550°C in air at 20ml / min for 5h to obtain a spherical catalyst, which was recorded as catalyst DB1#. Its catalytic performance is shown in Table 1.

[0060] Comparative Example 2:

[0061] Weigh 60g of copper-cerium modified molecular sieve catalyst, add 60g of aluminum sol, 1.5g of sesbania powder and mix well, add 0.5g of fatty alcohol polyoxyethylene ether and 35g of dilute phosphoric acid, and extrude into strips through a strip plate at a pressure of 7MPa to obtain a spherical catalyst precursor. Then, dry at 120°C for 6h, and calcine at 550°C in 20ml / min air for 5h to obtain a spherical catalyst, which is recorded as catalyst DB2#, and its catalytic performance is shown in Table 1.

[0062] Table 1

[0063]

[0064] The following Examples 11-12 and Comparative Example 3, respectively prepared catalysts were loaded into a tubular reactor to evaluate propane dehydrogenation reaction, wherein the composition of the feed gas was propane: nitrogen = 9:1; the space velocity was 800h -1 , reaction at normal pressure, propane volume space velocity is 1.5h -1 , the reaction temperature is 600° C. The specific test results are shown in Table 2.

[0065] Embodiment 11

[0066] The catalyst was prepared according to the method described in Example 1, except that 60 g of the catalyst weighed was SUZ-4 zeolite containing heteroatoms, denoted as catalyst 11#, and its catalytic performance is shown in Table 2.

[0067] Example 12

[0068] Weigh 60g of SUZ-4 zeolite catalyst containing heteroatoms, add 15g of kaolin, 1g of sesbania powder and mix well, add 1g of liquid paraffin and 50g of dilute nitric acid, squeeze into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 30MPa, and maintained for 2s to obtain a spherical catalyst precursor. Then it is dried at 120°C for 6h, and calcined at 550°C in 20ml / min air for 5 hours to obtain a spherical catalyst, recorded as catalyst 12#, and its catalytic performance is shown in Table 2.

[0069] Comparative Example 3:

[0070] Weigh 60g of heteroatom-containing SUZ-4 zeolite catalyst, add 15g of kaolin, 1g of sesbania powder and mix well, add 1g of liquid paraffin and 50g of dilute nitric acid, and extrude into strips through a strip plate at a pressure of 7MPa to obtain a spherical catalyst precursor. Then, dry at 120°C for 6h, and calcine at 550°C in 20ml / min air for 5h to obtain a spherical catalyst, which is recorded as catalyst DB3#, and its catalytic performance is shown in Table 2.

[0071] Table 2

[0072]

[0073] In the following Examples 13 to 15 and Comparative Example 4, the catalysts prepared in each case were loaded into a tubular reactor to evaluate the methanol to aromatics reaction, wherein the methanol space velocity was 2 h -1 , the reaction pressure is 1.5MPa, the reaction temperature is 400℃, and the specific test results are shown in Table 3.

[0074] Embodiment 13

[0075] The catalyst was prepared according to the method described in Example 1, except that the 60 g catalyst weighed was hydrogen-type ZMS-5 molecular sieve, denoted as catalyst 13#, and its catalytic performance is shown in Table 3.

[0076] Embodiment 14

[0077] Weigh 60g hydrogen-type ZMS-5 molecular sieve catalyst, add 15g kaolin, 1g methyl cellulose and mix well, add 1g magnesium stearate and 35g dilute phosphoric acid, squeeze into strips through a strip orifice plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 20MPa, and maintained for 2s to obtain a spherical catalyst precursor. Then it is dried at 120°C for 6h, and roasted at 550°C in 20ml / min air for 5 hours to obtain a spherical catalyst, recorded as catalyst 14#, and its catalytic performance is shown in Table 3.

[0078] Embodiment 15

[0079] Weigh 60g hydrogen-type ZMS-5 molecular sieve catalyst, add 15g kaolin, 1g methyl cellulose and mix well, add 1g solid paraffin and 50g dilute nitric acid, squeeze into strips through a strip plate, and then crush and granulate in a pulverizer. After screening, a small particle sample of 40-300 mesh is obtained. The small particle sample is put into a spherical mold (a spherical sample tank symmetrical up and down), pressurized to 50MPa, and maintained for 1s to obtain a spherical catalyst precursor. Then it is dried at 120℃ for 6h, and calcined at 600℃ in 20ml / min air for 3 hours to obtain a spherical catalyst, recorded as catalyst 15#, and its catalytic performance is shown in Table 3.

[0080] Comparative Example 4:

[0081] Weigh 60g hydrogen-type ZMS-5 molecular sieve catalyst, add 15g kaolin, 1g methyl cellulose and mix well, add 1g fatty alcohol polyoxyethylene ether and 35g dilute phosphoric acid, and extrude into strips through a strip plate at a pressure of 7MPa to obtain a spherical catalyst precursor. Then, dry at 120°C for 6h, and calcine at 550°C in 20ml / min air for 5h to obtain a spherical catalyst, recorded as catalyst DB4#, and its catalytic performance is shown in Table 3.

[0082] Table 3

[0083]

[0084] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a spherical catalyst, characterized in that: At least the following steps are included: Step I: mixing the catalyst, the binder and the extrusion aid, adding an inorganic acid to obtain a mixed material; Step II: The mixed material obtained in step I is squeezed into thick strips through a perforated plate, crushed in a pulverizer, granulated and sieved to obtain a small particle sample; Step III: placing the small particle sample obtained in step II into a spherical mold and applying pressure to obtain a spherical sample; Step IV: drying and calcining the spherical sample obtained in step III to obtain a spherical catalyst.

2. The preparation method according to claim 1, characterized in that: The catalyst is selected from at least one of hydrogen-type zeolite, heteroatom-containing SUZ-4 zeolite, molecular sieve catalyst, non-metal modified molecular sieve catalyst, and metal modified molecular sieve catalyst; Preferably, the molecular sieve catalyst is selected from at least one of ZSM-5 molecular sieve, HY molecular sieve, H-MOR molecular sieve, 13X molecular sieve and NaY molecular sieve; Preferably, the metal in the metal-modified molecular sieve catalyst is selected from at least one of iron, cobalt, nickel, copper, silver and zinc.

3. The preparation method according to claim 1, characterized in that: The binder is selected from at least one of pseudo-boehmite, silica sol, alumina sol, γ-alumina and kaolin.

4. The preparation method according to claim 1, characterized in that: The extrusion aid is selected from at least one of solid paraffin, paraffin powder, magnesium stearate, calcium stearate, sodium stearate, starch, glucose, sesbania powder, cellulose, methyl cellulose, alkyl benzene sulfonate, liquid paraffin, and fatty alcohol polyoxyethylene ether.

5. The preparation method according to claim 1, characterized in that: The inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.

6. The preparation method according to claim 1, characterized in that: The small particle sample is 40 to 300 mesh; Preferably, the pressurizing pressure is 0.1 to 300 kN; Preferably, the pressurization time is 0.01 to 60 seconds.

7. The preparation method according to claim 1, characterized in that: The conditions of the drying are as follows: The drying temperature is 80-160°C; The drying time is 3 to 6 hours.

8. The preparation method according to claim 1, characterized in that: The conditions of the calcination are as follows: The calcination temperature is 500-750°C; The calcination time is 4 to 8 hours.

9. The preparation method according to claim 1, characterized in that: The porosity of the spherical catalyst is 40-50%; Preferably, the strength of the spherical catalyst is 100-250N / particle.

10. Use of a spherical catalyst obtained by any one of the preparation methods of claims 1 to 9 in a shell-and-tube reactor.